PERANCANGAN TABUNG MOTOR ROKET RX-150-LPN BERDASARKAN ANALISIS PERHITUNGAN DAN EKSPERIMEN - Bintoro, Atik (BRIN Publishing, 2003)
The rocket motor tube is primary construction of rocket motor, this function is as combustion propellant chamber. The inner pressure will be produced in the tube during the combustion process running and produce structural stress. That's why the tube design is necessary to look the tube endurance of the structural stress. Besides this, the structural weight factor often become constrains, cause the supply of the material structural has light and strength property was limited. Whit concern for the structural stress and the structural weigth, it has been design the tube of RX150-LPN rocket motor, by analysis and experiment method. The analysis method was run affinity by finite element method, and the experiment method affinity by static test of the rocket motor tube. The design has purposed to find the strength and stiffness tube construction and was made the material light relative property. From the design was found characteristic of the product design is in tin of wall= 33mm, inner diameter=15 cm, length of tube=1,4 m, material=alloy steel AISI H11, weigth=17 kg and the prototype has endurance with 35 kg per cm on inner pressure.